Соматична мутація R248C (742 C>T) гена FGFR3 за раку сечового міхура - Міщук, Я.М.; Серга, С.В.; Стаховський, Е.А.; Вітрук, Ю.В.; Кононенко, А.А.; Шкляр, С.Є.; Демидов, С.В.; Козерецька, І.А. (Фактори експериментальної еволюції організмів, 2016)
Aim. The aim of our study was to determine the frequency of FGFR3 R248C mutation in Ukrainian patients with a
bladder cancer. Methods. The mutation was detected by PCR with allele specific primers. We investigated mutation in
90 DNA samples of patients with bladder cancer. Results. The FGFR3 R248C mutation was found in 1 case of urothelial
carcinoma. Conclusions. We found 1 mutation in patient with muscle invasive tumor. The prognosis of the patient is
generally good.
Keywords: FGFR3, mutation frequency, bladder cancer.